Effect of carbon nanomaterial on latent heat storage performance of carbonate salts in horizontal concentric tube. (15th October 2019) - Tao, Y.B.; Liu, Y.K.; He, Y.L.
Abstract: During the preparation of nanocomposite phase change material (nanoCPCM), more attentions are focused on thermal conductivity. In fact, adding nanomaterial not only affects thermal conductivity, but also changes the other thermophysical properties of PCM and causes complicated effects on latent heat storage performance. In present study, melting behavior of pure phase change material and its four kinds of nanocomposites in a horizontal concentric tube were investigated and a new evaluation index was developed to examine the effects of nanomaterial on heat storage performance of nanoCPCM. The results show that both thermal conductivity and melting temperature have significant effects on nanoCPCM melting behavior and heat storage rate. Sometimes, although the thermal conductivity is enhanced, the heat storage rate is decreased due to its melting temperature increasing caused by nanomaterial. Especially, when the heat source temperature and PCM melting temperature is close, the variation of melting temperature is more significant. For example, nanoCPCM with SWCNT has the higher thermal conductivity, but its heat storage rate is slower than nanoCPCM with MWCNT, because of its higher melting temperature. Therefore, more attention must be paid to the variation of melting temperature caused by nanomaterial during the preparation and application of nanoCPCMs. Highlights: Details of NanoCPCM melting and LHS process are revealed. Thermal conductivity and melting temperature are key factors for LHS rate. More attention must be paid to melting temperature variation. An evaluation index for LHS performance is proposed. NanoCPCM with MWCNT has the optimum LHS performance.